1999
DOI: 10.1164/ajrccm.160.2.9808109
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcome after Pulmonary Thromboendarterectomy

Abstract: This study evaluated long-term outcome of pulmonary thromboendarterectomy (PTE) in patients with chronic thromboembolic pulmonary hypertension (CTEPH). Survival, functional status, quality of life, health care utilization, and relationships between these parameters and postoperative pulmonary hemodynamics were assessed. Questionnaires were mailed to 420 patients who were more than 1 yr post-PTE; 308 responded (mean age, 56 yr [range, 19-89 yr]; mean years since PTE, 3.3 [range, 1- 16]). Survival after PTE was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
160
5
10

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 288 publications
(183 citation statements)
references
References 10 publications
7
160
5
10
Order By: Relevance
“…These results are similar to those of Archibald and colleagues, 29 whose study showed that postoperative patients had significantly better SF-36 scores (except for mental health) compared with those of pre-operative patients. In addition, for those with relatively peripheral type, 6 of 11 survivors after the survey did not need oxygen therapy, but all medically treated patients needed to con- tinue oxygen therapy.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results are similar to those of Archibald and colleagues, 29 whose study showed that postoperative patients had significantly better SF-36 scores (except for mental health) compared with those of pre-operative patients. In addition, for those with relatively peripheral type, 6 of 11 survivors after the survey did not need oxygen therapy, but all medically treated patients needed to con- tinue oxygen therapy.…”
Section: Discussionsupporting
confidence: 90%
“…The 6-year survival rate for the surgically treated group was 78.6% for relatively peripheral type and 92.3% for central type, values which are close to that obtained by Archibald et al's study (ie, 75% 6-year survival rate). 29 However, medical treatment offered better survival for patients with relatively peripheral type and with a mean PPA of >30 mmHg when compared with previous reports. [13][14][15] Several issues need to be considered when interpreting the results.…”
Section: Discussionmentioning
confidence: 71%
“…In PAH, a pulmonary arteriopathy leads to progressively increasing pulmonary vascular resistance (PVR), resulting in right heart failure and early death. The emergence of targeted drug therapies for PAH since the late 1990s and pulmonary endarterectomy (PEA) as a definitive treatment for CTEPH revolutionised the previously limited options for patients [2][3][4]. Due to the rarity of these diseases, expense of therapies and required expertise, seven specialist PH centres that adhere to nationally agreed standards of care [5,6] were first designated in the UK in 2001.…”
mentioning
confidence: 99%
“…Dann wird das thrombembolische Material in die Gefäßwand eingebaut mit der Folge einer bleibenden Reduktion des Gesamtquerschnittes der Pulmonalisstrombahn. Beginnen diese thrombembolischen Veränderungen der Gefäßwand auf Höhe der Segmentarterien oder proximal davon, steht mit der pulmonalen Thrombendarteriektomie ein chirurgisches Verfahren zur Verfügung, das eine wirksame kausale Behandlung der Erkrankung mit guten Langzeitergebnissen erlaubt (Mayer et al, 1996;Moser et al, 1987;Archibald et al, 1999 (Frazier et al, 2000).…”
Section: Die Veränderungen Führen üBer Eine Reduktion Des Gefäßlumensunclassified
“…Die chirurgische pulmonale Thrombendarteriektomie (PTEA) ist eine effiziente Behandlungsoption, die bei ausgewählten Patienten mit Erfolg durchgeführt werden kann (Mayer et al, 1996;Moser et al, 1987;Archibald et al, 1999). Die…”
Section: Diskussionunclassified